2016
DOI: 10.3109/10641955.2015.1137586
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of L-arginine for preventing preeclampsia in high-risk pregnancies: A double-blind, randomized, clinical trial

Abstract: L-arginine is effective for preventing preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
2
40
0
3
Order By: Relevance
“…In a more recent clinical trial, supplementation with l ‐arginine in women who were at a high risk of developing preeclampsia significantly reduced blood pressure and preterm birth rates, and the number of women developing preeclampsia, while increasing birth weight relative to placebo‐treated women . The previous adverse effects listed by Vadillo‐Ortega et al, were absent in the more recent study, likely due to a reduction in the dose of l ‐arginine supplementation. However, dyspepsia was reported in the l ‐arginine–supplemented women, but was not severe enough to discontinue treatment.…”
Section: No Pathwaymentioning
confidence: 89%
See 1 more Smart Citation
“…In a more recent clinical trial, supplementation with l ‐arginine in women who were at a high risk of developing preeclampsia significantly reduced blood pressure and preterm birth rates, and the number of women developing preeclampsia, while increasing birth weight relative to placebo‐treated women . The previous adverse effects listed by Vadillo‐Ortega et al, were absent in the more recent study, likely due to a reduction in the dose of l ‐arginine supplementation. However, dyspepsia was reported in the l ‐arginine–supplemented women, but was not severe enough to discontinue treatment.…”
Section: No Pathwaymentioning
confidence: 89%
“…Unfortunately, one study using l ‐arginine and antioxidant supplementation reported numerous mild adverse effects, including headaches, palpitations, dizziness, and dyspepsia . In a more recent clinical trial, supplementation with l ‐arginine in women who were at a high risk of developing preeclampsia significantly reduced blood pressure and preterm birth rates, and the number of women developing preeclampsia, while increasing birth weight relative to placebo‐treated women . The previous adverse effects listed by Vadillo‐Ortega et al, were absent in the more recent study, likely due to a reduction in the dose of l ‐arginine supplementation.…”
Section: No Pathwaymentioning
confidence: 92%
“…Thus, the prediction of preeclampsia is paramount in performing appropriate procedures to reduce the prevalence of the disease by modifying antenatal care and pharmacological interventions in a timely manner. 9,10 Several clinical, biochemical and biophysical tests have been proposed to predict PE; however, none of them have proved to be useful in isolation to classify the preexisting maternal risk for PE with sufficient specificity and sensitivity for clinical use. Ideally, the predictive model should be simple, inexpensive, and easy to apply, so that it can be widely used in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress of the placenta is able to result in endothelial dysfunction. Several important antioxidants, such as superoxide dismutase (SOD) and glutathione peroxidase (GPx), are significantly decreased in the maternal circulation of women with preeclampsia [ 4 ]. A simple in vitro model wherein endothelial cell monolayers are exposed to hypoxia/reoxygenation (H/R) is widely used to mimic the microvascular dysfunction that is induced by oxidative stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%